Incidence of Anxiety in Patients with Multiple Sclerosis (MS) - Green, Rivka; Kalina, Jennifer; Pandey, Krupa (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Objective: To investigate the (1) incidence of anxiety and (2) association of anxiety with disease duration, depression, and age in an outpatient Multiple Sclerosis (MS) Center. Background: The incidence of anxiety varies in the literature but is estimated to affect 44.5% of people with MS. Anxiety can be a predictor of poor Quality of Life, especially relevant in progressive illnesses, such as MS. Though research has shown that patients newly diagnosed experience higher anxiety levels, the relationship between anxiety and disease duration is unclear. Since anxiety can be comorbid with depression in MS populations, it is relevant to establish its association in this setting. Finally, though anxiety usually increases in older age, research for this relationship in MS populations is inconclusive. Design/Methods: The commonly used Hospital Anxiety and Depression Scale, was distributed once to patients with MS over a 3 month period to assess anxiety and depression scores. MS disease duration and age were confirmed by neurologists. Results: Out of 160 patients with MS who completed the HADS, 19% reported abnormal anxiety, 14% reported borderline cases of anxiety, and 67% did not report anxiety. After following up on significant correlations, depression and younger age were related to higher anxiety levels, (R2=.35, F(4,144)=19.26, p<0.001). The standardized partial regression coefficients indicated 2 statistically significant predictors, depression (β=.55, p=<.001) and age (β=-.25, p=<.001). Discussion: 33% of patients reported symptoms of anxiety, emphasizing the need to focus on treating anxiety, specifically, early in their disease course. Clinicians may also want to recognize that elevated depression scores predicted anxiety. Lastly, in our cohort, the younger population reported higher anxiety, demonstrating that progressive illnesses may affect anxiety levels in younger populations more. Since approximately one third of patients with MS expressed anxiety symptoms, it is important to incorporate this into treatment plans.